Gate‐controlled series capacitor: A new methodology for mitigating sub‐synchronous resonance in a series‐compensated DFIG‐based wind farm - Mohamed Abdeen; Mahmoud A. El‐Dabah; Jose Luis Domínguez‐García; Salah Kamel (IET Renewable Power Generation, 2023)
Abstract Series‐compensated transmission lines can lead to a sub‐synchronous resonance (SSR) phenomenon at high compensation levels, where the system lacks stability. Gate‐controlled series capacitor (GCSC) is widely used to damp the SSR. Here, an effective and new methodology for damping the SSR is presented. The proposed method aims to alleviate the SSR phenomenon based on estimating both the frequency and the maximum value of the voltage magnitude signal rather than using the Proportional Integral controller. The appropriate turn‐off angle corresponding to the maximum value of the voltage magnitude signal is applied to the GCSC on the condition that the estimated frequency of the voltage magnitude signal is within the range of the SSR frequency. If the estimated frequency of the voltage magnitude signal is out of the range of the SSR frequency, the steady‐state turn‐off angle (1130) is applied to the GCSC. The capability of the proposed method for damping the SSR under various compensation levels, various wind speeds, and sub‐synchronous control interaction (SSCI) is validated by time‐domain simulation and eigenvalue analysis. Compared to the presented latest method for SSR damping using GCSC, all the obtained results demonstrate that the oscillations converge faster when the proposed method is activated.